ChemInform Abstract: A Tandem Reaction of Benzyne with Functionalized Benzylidenephthalan to Afford Phenanthro[10, 1‐bc]furan. Issue 30 (29th July 2014) - Siyang, Hai Xiao; Wu, Xu Rui; Liu, Hui Ling; Wu, Xin Yan; Liu, Pei Nian
Abstract The title reaction provides highly concise and effective routes to related complex compounds including natural product derivatives.